对公式∀x(F(x)→G(x,y))∧H(x,y)做代替,则下面公式中正确的是( )。
A: ∀x(F(x)→G(x,y))∧H(z,y)
B: ∀x(F(x)→G(y,z))∧H(u,y)
C: ∀z(F(z)→G(x,y))∧H(y,y)
D: ∀z(F(x)→G(z,y))∧H(x,y)
A: ∀x(F(x)→G(x,y))∧H(z,y)
B: ∀x(F(x)→G(y,z))∧H(u,y)
C: ∀z(F(z)→G(x,y))∧H(y,y)
D: ∀z(F(x)→G(z,y))∧H(x,y)
举一反三
- 公式"x ( F(x,y,z ) → "y ( G(x,y,z) → "z H(x,y,z) ) )的前束范式为 A: "x$y$z (F(x,t,w) → ( G(x,y,w ) → H(x,y,z) ) ) B: $x$y$z (F(x,t,w) → ( G(x,y,w ) → H(x,y,z) ) ) C: "x"y$z (F(x,t,w) → ( G(x,y,w ) → H(x,y,z) ) ) D: "x$y"z (F(x,t,w) → ( G(x,y,w ) → H(x,y,z) ) )
- 在谓词公式("x)(F(x)ÞG(y))Þ($y)(H(x)∧L(x,y,z))中,("x)的辖域是() A: (F(x)ÞG(y)) B: F(x) C: (F(x)ÞG(y))Þ($y)(H(x)∧L(x,y,z)) D: ("x)(F(x)
- 在谓词公式("x)(F(x)ÞG(y))Þ($y)(H(x)∧L(x, y, z))中,($y)的辖域是( ) A: F(x) B: ("x)(F(x) C: (H(x)∧L(x, y, z)) D: (F(x)ÞG(y))
- 在谓词公式("x)(F(x)ÞG(y))Þ($y)(H(x)∧L(x, y, z))中,("x)的辖域是( ) A: (F(x)ÞG(y)) B: F(x) C: (F(x)ÞG(y))Þ($y)(H(x)∧L(x, y, z)) D: ("x)(F(x)
- 公式∀x(F(x,y,z)→G(x,y))∧H(x,y,z)中,x约束出现 次。